1992
DOI: 10.1073/pnas.89.8.3367
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian inheritance of familial prostate cancer.

Abstract: Previous studies have demonstrated familial clustering of prostate cancer. To define the nature of this familial aggregation and to assess whether Mendelian inheritance can explain prostate cancer clustering, proportional hazards and segregation analyses were performed on 691 families ascertained through a single prostate cancer proband. The proportional hazards analyses revealed that two factors, early age at onset of disease in the proband and multiple affected family members, were important determinants of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
372
3
41

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 645 publications
(423 citation statements)
references
References 33 publications
7
372
3
41
Order By: Relevance
“…This elaborate multi-institutional network was designed to recruit African-American families that fulfill very stringent criteria for hereditary prostate cancer, exceeding those originally proposed by Carter et al 10 The AAHPC inclusion criteria were as follows: (a) African-American families with four or more members diagnosed with prostate cancer, (b) the combined age at diagnosis of all affected members in the family should average 65 y or less, (c) at least three affected members must donate a sample of blood for genotyping. These criteria differ from the original HPC definition proposed by Carter et al, 7,10 in which the hereditary subgroup consisted of three successive generations with prostate cancer, a clustering of three or more affected individuals in a nuclear family and/or two relatives with early onset (less than 55 y) of prostate cancer. The details of the AAHPC network infrastructure and recruitment protocols have been previously reported.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…This elaborate multi-institutional network was designed to recruit African-American families that fulfill very stringent criteria for hereditary prostate cancer, exceeding those originally proposed by Carter et al 10 The AAHPC inclusion criteria were as follows: (a) African-American families with four or more members diagnosed with prostate cancer, (b) the combined age at diagnosis of all affected members in the family should average 65 y or less, (c) at least three affected members must donate a sample of blood for genotyping. These criteria differ from the original HPC definition proposed by Carter et al, 7,10 in which the hereditary subgroup consisted of three successive generations with prostate cancer, a clustering of three or more affected individuals in a nuclear family and/or two relatives with early onset (less than 55 y) of prostate cancer. The details of the AAHPC network infrastructure and recruitment protocols have been previously reported.…”
Section: Introductionmentioning
confidence: 87%
“…Affected males from families with hereditary prostate cancer (HPC) account for 5-10% of all reported cases of prostate cancer in the United States and Europe. [7][8][9] It is against this background that the African-American Hereditary Prostate Cancer Study (AAHPC) was initiated to recruit African-American families to a hereditary prostate cancer study. This is the first large-scale study to describe the clinical characteristics of hereditary prostate cancer in affected African-American men from multiplex families.…”
Section: Introductionmentioning
confidence: 99%
“…19 Colorectal cancer risk assessment was based on the Scheuner criteria, which classifies individuals as general population, moderate and high risk (Supplementary Table 1). Participants' medical and family histories were then re-examined for evidence of hereditary risk.…”
Section: Cancer Risk Assessmentmentioning
confidence: 99%
“…However, it is clear that there are subtypes of the disease involving familial clustering 2 and a hereditary form accounts for about 9% of cases. 3 The marked variation in the incidence and mortality from prostate cancer across geographic and ethnic groups and the observed changes in risk in migrants 4 suggest that dietary and/or lifestyle factors affect prostate cancer development. Dietary factors may prove to be directly protective against prostate cancer development or may protect against tumour progression as proposed by Carter et al 5 They reported that histological prostate cancer was as common in Japan as in the United States, but that in Japan the cancer remained latent and rarely progressed to clinically manifested disease.…”
Section: Reviewmentioning
confidence: 99%